2008
DOI: 10.1074/jbc.m806179200
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of HNF-4 and Foxo1 Is Required for Reciprocal Transcriptional Regulation of Glucokinase and Glucose-6-phosphatase Genes in Response to Fasting and Feeding

Abstract: Glucokinase (GK) and glucose-6-phosphatase (G6Pase) regulate rate-limiting reactions in the physiologically opposed metabolic cascades, glycolysis and gluconeogenesis, respectively. Expression of these genes is conversely regulated in the liver in response to fasting and feeding. We explored the mechanism of transcriptional regulation of these genes by nutritional condition and found that reciprocal function of HNF-4 and Foxo1 plays an important role in this process. In the GK gene regulation, Foxo1 represses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 47 publications
6
100
0
2
Order By: Relevance
“…Glucose-6-phosphatase gene expression is repressed by TCF7L2 independently of FOXO1 Expression of G6PC is regulated by FOXO1 and HNF4α [30], and the β-catenin-FOXO1 complex stimulates G6PC only in the absence of insulin [24]. We observed that in HepG2 cells with reduced TCF7L2 expression, G6PC mRNA expression was increased independently of the presence or absence of insulin (Fig.…”
Section: Statistical Analysesmentioning
confidence: 52%
See 1 more Smart Citation
“…Glucose-6-phosphatase gene expression is repressed by TCF7L2 independently of FOXO1 Expression of G6PC is regulated by FOXO1 and HNF4α [30], and the β-catenin-FOXO1 complex stimulates G6PC only in the absence of insulin [24]. We observed that in HepG2 cells with reduced TCF7L2 expression, G6PC mRNA expression was increased independently of the presence or absence of insulin (Fig.…”
Section: Statistical Analysesmentioning
confidence: 52%
“…4a). To further characterise the effect of TCF7L2 on G6PC expression, we measured G6PC promoter activity by using luciferase reporter constructs previously used to analyse the synergistic activation of HNF4α and FOXO1 [30]. In HepG2 cells treated with TCF7L2 siRNA, both the wild-type G6PC promoter and the G6PC promoter construct lacking the FOXO1 binding region (G6PCΔ123) showed a Representative western blots of total cell lysate from HepG2 cells cultured as above (a-f) similar increase in luciferase activity (Fig.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Glutathione S-Transferase (GST) Pulldown Assays-GST-ERR␥ (Dr. Uwe Borgmeyer), GST-LRH-1 (Dr. Timothy Osborne), GST-HNF4␣ (Dr. Akiyoshi Fukamizu), and GST-EID1 (Dr. Eckardt Treuter) were generously provided as indicated (23)(24)(25)(26). MagneGST TM Pull-Down System (catalog #V8872, Promega) was used in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This effect may be regulated by FoxO1 35) and Nrf2 36) transcription factors. Interestingly, HNF-4α can interact with FoxO1 and modulate its transcriptional activity 37) . Moreover, levels of Nrf2 may be regulated by HNF-4α 38) .…”
Section: Potential Role Of Hnf-4α In the Suppression Of Tumor Developmentioning
confidence: 99%
“…This is probably because, in the absence of DNA damage, HNF-4α is activated by PGC-1α; whereas, under DNA damage conditions, HNF-4α would switch its interaction partner for FoxO1, p53, or Rad50 to activate the DNA damage response. Indeed, HNF-4α interaction with FoxO1 has been shown to decrease transcriptional activity for certain target genes 37) .…”
Section: Potential Role Of Hnf-4α In the Suppression Of Tumor Developmentioning
confidence: 99%